The Role of Advocacy on Ethical and Legal Problems in the Hospital - Redyanto Sidi; Helminur Iskandar Sinaga; Chandra Istanti Prasetyo; Jerry Fitrio Julianto Tobing; Hottua Sihotang; Mahzul Harahap (Budapest International Research and Critics University, 2021)
In carrying out their duties and professions, it is possible for a health worker to experience ethical and legal problems in a hospital and have to deal with the Hospital Ethics and Legal Committee. Considering the role of legal consultants and legal advisors in providing legal advice, what is the role of both of them in ethical and legal issues experienced by Health Workers in hospitals. Therefore, this study aims to identify and analyze the role of legal consultants and legal advisors on ethical and legal issues in hospitals. The research method used is normative juridical which is carried out by examining legal principles, concepts, theories and laws and regulations. Advocates in dealing with ethical and legal issues in hospitals play a role in improving order and legal certainty within the hospital. In this case, an advocate can provide legal assistance, legal consultation, legal protection during the provision of legal aid, and other matters relating to the provision of legal assistance to clients. However, in dealing with these problems, the role of legal consultants is narrower, which is only limited to providing legal assistance and/or legal services outside the court.